A novel disposable ring (Circumplast) showed no ring migration onto the shaft of the penis in first 1000 male children's circumcisions in a community specialist clinic - Atif Saeed; Darrel Gregory; Ruhul Amin; Murtaza Khanbhai; Abdul Khan (Elsevier, 2023)
Male children circumcision is a frequently performed surgical procedure in the community. The Plastibell is the established device commonly used in the UK and USA. Migration of the Plastibell ring onto the penile shaft is a rare but serious risk. Proximal migration can lead to glans incarceration requiring urgent ring removal. Impaction and migration may be attributable to penile oedema, erection, incorrect ring sizing, excessive traction on the foreskin and intrinsically to the Plastibell's shape and design. We present our experience of the first 1000 circumcisions performed with a novel Circumplast device at our community clinic over two years. All circumcisions were performed under local anaesthesia by trained doctors with the backup of a paediatric surgeon. Data was collected prospectively. We assessed early and late complications of Circumplast circumcision. Follow-up consultations/visits were arranged if required. No episode of proximal ring migration or glans impaction was observed for male children circumcision was performed with a Circumplast device.